2020
DOI: 10.21203/rs.3.rs-41506/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modified CBT for Social Anxiety and Social Functioning in Young Adults with Autism Spectrum Disorder

Abstract: Background: There is a strong research imperative to investigate effective treatment options for adolescents and adults with Autism Spectrum Disorder (ASD). Elevated social anxiety, difficulties with social functioning, and poor mental health have all been identified as core treatment targets for this group. While theoretical models posit a strong bidirectionality between social anxiety and ASD social functioning deficits, few interventions have targeted both domains concurrently. Of the two group intervention… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…While no statistically significant changes were observed in social aspects of autism, such as social cognition, social awareness, or communication, significant improvements were found in AM, related to cognitive and behavioral inflexibility. The finding is in line with research on modified CBT for autistic individuals, which has observed changes in the SRS subscales of social motivation and AM but not overall social functioning (Bemmer et al, 2021). Also, this result may align with the NeuroACT program's overarching treatment goal of making social difficulties less of an obstacle to being active in social relationships without training the social skills themselves.…”
Section: Discussionsupporting
confidence: 87%
“…While no statistically significant changes were observed in social aspects of autism, such as social cognition, social awareness, or communication, significant improvements were found in AM, related to cognitive and behavioral inflexibility. The finding is in line with research on modified CBT for autistic individuals, which has observed changes in the SRS subscales of social motivation and AM but not overall social functioning (Bemmer et al, 2021). Also, this result may align with the NeuroACT program's overarching treatment goal of making social difficulties less of an obstacle to being active in social relationships without training the social skills themselves.…”
Section: Discussionsupporting
confidence: 87%
“…Given evidence suggesting that individuals with ASD may report higher levels of social anxiety when they are describing core ASD characteristics such as social difficulties (Spain et al, 2018), it is possible that participants with ASD may have reported increased social anxiety symptoms that were actually more reflective of ASD symptoms. However, a bidirectional link between social anxiety and social impairment in ASD has been proposed as a key contributor to the high prevalence of social anxiety in ASD (Bemmer et al, 2021; White et al, 2014). The social difficulties commonly seen in ASD may contribute to the development and maintenance of SAD, and this elevated anxiety may subsequently exacerbate pre‐existing social difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that the social networks of autistic adults may be enhanced through classes and low level community interventions, such as providing one-to-one personalized support and opportunities to participate in peer groups and social activities (McConkey et al, 2021). In addition, cognitive behavior therapy (CBT)-type approaches have been found to be effective for social anxiety and to improve social motivation (Bemmer et al, 2021), and interventions such as PEERS and Circles have been found to improve friendship quality and conversational skills in adolescents and young adults aged 15–26 years old (Rose et al, 2021; Wyman & Claro, 2020). Job-based social skills interventions have also been found to improve autistic adults’ social-pragmatic skills such as social awareness, reciprocal social communication, and social avoidance (Gorenstein et al, 2020).…”
Section: Discussionmentioning
confidence: 99%